A sonoridade da viola de arame na composição do ciclo Genesis - Alves, Jorge José Ferreira de Lima (2009)
This work deals with the compositional principles and techniques used to create a cycle of pieces written by the author and named Genesis. This cycle consists of four pieces for Viola de Arame (Brazilian Viola) solo, Viola de Arame and flute, and Viola de Arame accompanied by two instrumental ensembles (Genesis II and Genesis IV). The compositional process applied on the Cycle was a result of a research on the application of the sonority of the Brazilian Viola as sound material, making use of techniques from the so-called Spectral Music. The theoretical groundwork for the comprehension of spectral music was found in Tristan Murail (1993), François Rose (1996) and Joshua Fineberg (2000), among other authors. Based on this set of references, the compositional processes applied to Genesis were analyzed and registered, from the most elementary procedures, such as the usage of the harmonic series applied on the first piece, to the most specific one, such as ring modulation, used in Genesis II and Genesis III. The fourth piece was composed using a computer program for spectral analysis, editing, and synthesis. The resultant material produced by the application of this piece of software on sounds from the Brazilian Viola was used to construct and analyze sound aggregates that were considered raw material of the composition process.